A real-time XML protocol for bridging virtual communities. (1st January 2011) - King, James; Kawash, Jalal
Virtual communities play an increasingly important and prevalent role in our daily lives. However, these communities are often closed relative to each other, forming independent islands of communities. Yet, this independence is artificially imposed on such communities by closed support software or policies since the purposes or member-bases of these communities often overlap. Our objective is to bridge these virtual communities, allowing them to seamlessly and securely mesh in spite of their differing implementations and autonomous policies. Our Object-Subscription Protocol is an attempt in this bridging direction.